Compositions and methods for electrodeposition of nanotwinned copper
Patent Information
- Application Number
- JP2023511565
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-28
- Filing Date
- 2021-08-25
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-08-25
Smart Images

Figure 0007652245000001 
Figure 0007652245000002 
Figure 0007652245000003
Abstract
Description
[Technical field]
[0001] The present invention relates generally to the electrodeposition of nanotwinned copper and to electrolytic copper plating baths for producing nanotwinned copper deposits. [Background technology]
[0002] Electrochemical deposition processes are well established in integrated circuit manufacturing: copper lines are formed by plating metal into very thin, high aspect ratio trenches and vias in a process commonly referred to as "damascene" processing (pre-passivation metallization).
[0003] Copper is one of the most essential conductors in microelectronic devices due to its high ductility and electrical conductivity. With the advancement of microelectronics, there is a constant need to create smaller and denser interconnect structures. One way to this goal is to eliminate the solder between two separate substrates that connect copper vias, pads, bumps, or pillars, which can be achieved, for example, by the process of Cu-Cu hybrid bonding.
[0004] Due to the combination of excellent mechanical properties, good electrical conductivity, and unique structure, nanotwinned copper has attracted attention for use in microelectronics.
[0005] In particular, the mechanical strength of metallic materials such as copper generally increases when the grain size is reduced to the nanoscale level. Nanotwinned copper describes ultrafine-grained copper whose grains contain a high density of lamellar nanoscale twins separated by tightly packed twin boundaries. By introducing nanoscale twins into the copper microstructure, properties such as mechanical strength, ductility, electromigration resistance, and hardness can be improved.
[0006] Some nanoscale metal thin films may even have specific mechanical properties. As a result, it has been found that metals with nanotwin crystalline properties may be suitable for applications such as through silicon vias, semiconductor chip interconnects, packaging substrate pin through holes, metal interconnects (e.g., copper interconnects), or metal materials on substrates.
[0007] Nanotwinned copper can be achieved in several ways, including, for example, sputtering and electrolytic deposition. One of the advantages of sputtering is the high purity in the copper film, along with the ability to follow the preferred orientation of the grains. Sputtered (111)-oriented nanotwinned copper has been shown to have high thermal stability and strength. On the other hand, direct current electrolytic plating is well suited for industrial mass production, and electroplated nanotwinned copper can be classified into two groups: equiaxed grain nanotwinned copper and (111)-oriented nanotwinned copper.
[0008] Crystal defects can affect the mechanical, electrical, and optical properties of materials. Twinning can occur in materials where two parts of the crystal structure are symmetrically related to each other. In face-centered cubic (FCC) crystal structures, including copper, tight twin boundaries can form as (111) mirror planes where the typical stacking order of the (111) planes is reversed. In other words, adjacent grains are mirrored across tight twin boundaries in a layered (111) structure. The twins grow in a layered manner extending along the lateral (111) crystal planes, and the twin thickness is on the order of nanometers, hence the term "nanotwinned". Nanotwinned copper (nt-Cu) exhibits excellent mechanical and electrical properties and can be used in a wide variety of applications in wafer-level packaging and advanced packaging design.
[0009] Compared to copper with conventional grain boundaries, nanotwinned copper has strong mechanical properties including high strength and high tensile ductility. Nanotwinned copper also demonstrates high electrical conductivity, which may be due to twin boundaries, which cause less significant electron scattering compared to grain boundaries. Furthermore, nanotwinned copper exhibits high thermal stability, which may be due to twin boundaries, which have an excess energy that is orders of magnitude lower than that of grain boundaries. In addition, nanotwinned copper allows high copper atomic diffusivity, which is useful for copper-copper direct bonding. Nanotwinned copper also exhibits high resistance to electromigration, which may be a result of twin boundaries slowing down electromigration-induced atomic diffusion. Nanotwinned copper has demonstrated strong resistance to seed etching, which may be important in fine line redistribution layer applications. Nanotwinned copper also exhibits low impurity incorporation, which results in fewer Kirkendall voids as a result of the soldering reaction with nanotwinned copper.
[0010] In some implementations, nanotwinned copper allows for direct copper-copper bonding. Such copper-copper bonding can be performed at low temperatures, moderate pressures, and lower bonding forces / times. Typically, deposition of copper structures results in a rough surface. In some implementations, electrodeposition of nanotwinned copper prior to copper-copper bonding may be followed by an electropolishing process to achieve a smooth surface. Nanotwinned copper structures with smooth surfaces can be used in copper-copper bonding with shorter bonding times, lower temperatures, and fewer voids.
[0011] US Patent No. 7,074,315 to Desmaison et al., the entire subject matter of which is incorporated herein by reference, describes a copper electrolyte for depositing matte layers of copper. The electrolytic copper plating bath contains at least one polyhydroxyl compound selected from poly(1,2,3-propanetriol), poly(2,3-epoxy-1-propanol), and derivatives thereof to produce copper deposits that are matte and exhibit uniform, low roughness, and provide sufficient adhesion of organic coatings without additional pretreatment. However, the use of a copper electrolyte for depositing nanotwinned copper is not suggested.
[0012] WO 2020 / 092244 to Banik et al., the entire subject matter of which is incorporated herein by reference, describes copper structures having a high density of nanotwinned copper deposited on a substrate. Banik does not describe a particular electrolytic copper plating bath, but instead describes electroplating conditions that include applying a pulsed current waveform that alternates between constant and no current, the duration of which no current is applied being substantially longer than the duration of which the constant current is applied.
[0013] Yang, U.S. Patent No. 10,566,314, the entire subject matter of which is incorporated herein by reference, describes how a columnar grain microstructure is the optimal copper grain structure for Cu-Cu metallurgy for metallurgical joining. The disclosed copper grain microstructure plated with an inhibitor-only system produces a columnar grain structure as a result of plating nanotwinned copper. Although columnar grains are mentioned, the (111) copper grain structure of nanotwinned copper is not mentioned.
[0014] Thus, there remains a need in the art for improved electrolytic copper solutions for producing nanotwinned copper deposits. In addition, there remains a need in the art for improved electrolytic copper solutions that can deposit nanotwinned copper in a (111) orientation and with a high percentage of nanotwins. Summary of the Invention
[0015] It is an object of the present invention to provide an improved copper electroplating solution.
[0016] Another object of the present invention is to provide a copper electroplating solution capable of producing nanotwinned copper in the deposit.
[0017] It is yet another object of the present invention to provide nanotwinned copper with a (111) orientation.
[0018] It is yet another object of the present invention to provide a copper deposit having a high density of nanotwin crystals.
[0019] To that end, in one embodiment, the present invention generally relates to a copper electroplating solution used to produce nanotwinned copper, typically comprising: A) a copper salt; B) a source of halide ions; C) a linear or branched polyhydroxyl.
[0020] In another embodiment, the present invention also generally relates to a method of producing copper deposits having a high density of nanotwin crystals using the copper electroplating solutions described herein. [Brief description of the drawings]
[0021] [Figure 1] 1 shows an SEM (30 pm width at 10K magnification) of a copper deposit produced according to Comparative Example 1. [Diagram 2] 1 shows an SEM (30 pm wide at 10K magnification) of a copper deposit produced according to Example 2. [Diagram 3] 1 shows an SEM (30 pm width at 10K magnification) of a copper deposit produced according to Comparative Example 3. [Figure 4] 1 shows an SEM (60 pm width at 5K magnification) of a copper deposit produced according to Comparative Example 4. [Diagram 5] 1 shows an SEM (75 pm wide at 4K magnification) of a copper deposit produced according to Example 5. [Figure 6] 1 shows an SEM (50 pm width at 6K magnification) of a copper deposit produced according to Example 6. [Figure 7] 1 shows an SEM (30 pm wide at 10K magnification) of a copper deposit produced according to Example 7. [Figure 8] 1 shows the grain orientation of a copper deposit produced according to Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present inventors have discovered that electrodeposition of high density (111) oriented nanotwinned copper may enable smaller and denser interconnect structures between two separate substrates used to connect copper vias, pads, bumps, pillars, etc., via Cu-Cu hybrid bonding.
[0023] As used herein, "a," "an," and "the" refer to both the singular and the plural, unless the context clearly dictates otherwise.
[0024] As used herein, the term "about" refers to a measurable value of a parameter, amount, duration, etc., and is meant to include no more than + / -15% variation, preferably no more than + / -10% variation, more preferably no more than + / -5% variation, even more preferably no more than + / -1% variation, and even more preferably no more than + / -0.1% variation of and from the specifically recited value, so long as such variations are appropriate to practice the invention described herein. It is further to be understood that the values referred to by the modifier "about" are themselves specifically disclosed herein.
[0025] As used herein, spatially relative terms such as "beneath," "below," "lower," "above," "upper," and the like are used for ease of description to describe the relationship of one element or feature to another element or feature as illustrated in the figures. It is further understood that the terms "front" and "back" are not intended to be limiting and are intended to be interchangeable where appropriate.
[0026] As used herein, the terms "comprises" and / or "comprising" specify the presence of stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof.
[0027] As used herein, the terms "substantially free" or "essentially free" with respect to a particular element or compound, unless otherwise defined herein, mean that the given element or compound is not detectable by conventional analytical means well known to those skilled in the art of metal plating for bath analysis. Such methods typically include atomic absorption spectroscopy, titration, UV-Vis analysis, secondary ion mass spectrometry, and other commonly available analytical techniques.
[0028] All amounts are percent by weight unless otherwise specified. All numerical ranges are inclusive and combinable in any order, except where it is logical that such numerical ranges are constrained to add up to 100%.
[0029] The terms "plating" and "depositing" or "deposition" are used interchangeably throughout this specification. The terms "composition" and "bath" and "solution" are used interchangeably throughout this specification. The term "alkyl", unless otherwise stated herein as having substituents, is composed solely of carbon and hydrogen and has the general formula: C n H 2n+1 The term "average" is equivalent to the average value of a sample. All amounts are weight percent unless otherwise specified. All numerical ranges are inclusive and combinable in any order, except where it is logical that such numerical ranges are constrained to add up to 100%.
[0030] In one embodiment, the present invention generally relates to the electrodeposition of nanotwinned copper, and the copper electroplating solution used to produce nanotwinned copper typically comprises: A) a copper salt; B) a source of halide ions; C) linear or branched polyhydroxyl.
[0031] In a preferred embodiment, the copper salt comprises copper sulfate. Other copper salts that may be used in the composition include copper methanesulfonate, copper pyrophosphate, copper propanesulfonate, and other similar compounds. The concentration of copper sulfate in the electroplating solution generally ranges from about 1 to about 100 g / L, more preferably from about 20 to about 80 g / L, and most preferably from about 40 to about 60 g / L.
[0032] The halide ions may act as bridges to aid in the adsorption of certain organic additives onto the substrate surface. Halide ions include, but are not limited to, chloride ions, bromide ions, iodide ions, and combinations thereof. In one embodiment, the halide ions include chloride ions. The concentration of chloride ions in the electroplating solution is generally within the range of about 1-150 mg / L, more preferably about 30-120 mg / L, and most preferably about 45-75 mg / L.
[0033] The linear or branched polyhydroxyl generally has a molecular weight of about 200 to about 20,000 g / mol, more preferably about 500 to about 5,000 g / mol, and most preferably about 1,000 to about 3,000 g / mol. In a preferred embodiment, the linear or branched polyhydroxyl comprises poly(2,3-epoxy-1-propanol). In one embodiment, the concentration of the linear or branched polyhydroxyl is within the range of about 1 to about 10,000 mg / L, more preferably about 10 to about 1,000 mg / L, and most preferably about 50 to about 600 mg / L.
[0034] In addition, the electroplating composition may contain an acid to control the conductivity of the plating bath, and suitable acids include sulfuric acid and methanesulfonic acid. In one embodiment, the acid is sulfuric acid. The concentration of the acid in the electroplating solution is generally in the range of about 0 to about 240 g / L, more preferably in the range of about 10 to about 180 g / L, and most preferably in the range of about 80 to about 140 g / L.
[0035] The inventors have also surprisingly found that the properties of nanotwinned copper can be improved by reacting amine-based or ammonium alcohols with 2,3-epoxy-1-propanol. These polyhydroxyl compounds initiated by cores containing nitrogen species can increase the columnar nanotwinned copper density and help initiate nanotwinned copper more quickly than poly(2,3-epoxy-1-propanol).
[0036] Examples of these amine-based alcohols include, but are not limited to, ethanolamine, diethanolamine, triethanolamine, propanolamine, isopropanolamine, diisopropanolamine, triisopropanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N-propyldiethanolamine, methylmonoethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N-propylmonoethanolamine, N-propyldiethanolamine, N-butylethanolamine, N-butyldiethanolamine, N,N-dibutylethanolamine, hydroxyethylmorpholine, 2-piperidinoethanol, diethanolisopropanolamine, N-(2-hydroxyethyl)pyrrolidine, and combinations of the foregoing.
[0037] Additionally, aminic alcohols can be converted to ammonium salts by quaternizing the nitrogen, for example, by means of a methylating agent such as dimethyl sulfate.
[0038] Examples of ammonium alcohols include, but are not limited to, choline chloride, b-methylcholine chloride, bis(2-hydroxyethyl)dimethylammonium chloride, tris(2-hydroxyethyl)methylammonium chloride, carnitine chloride, (2-hydroxyethyl)dimethyl(3-sulfopropyl)ammonium chloride, and combinations of the foregoing.
[0039] When reacting an amine-based alcohol or ammonium alcohol with 2,3-epoxy-1-propanol, the molar ratio of amine to 2,3-epoxy-1-propanol is generally in the range of about 0.01 to 0.50, more preferably in the range of 0.01 to 0.20, and more preferably in the range of 0.01 to 0.10.
[0040] The inventors have also found that the introduction of other organic electroplating compounds can destroy the ability of the polyhydroxyl material to produce nanotwinned copper. These prohibited compounds include accelerators, brighteners, carriers, wetting agents, and / or leveling agents. Thus, in a preferred embodiment, the electroplating solution is at least substantially free of any accelerators, brighteners, carriers, wetting agents, and / or leveling agents, or any compounds that may function as accelerators, brighteners, carriers, wetting agents, and / or leveling agents. By "substantially free," we mean that the electroplating solution contains less than 20 ppm, more preferably less than about 10 ppm, and most preferably less than about 3 ppm of any compounds that may function as accelerators, brighteners, carriers, wetting agents, and / or leveling agents.
[0041] In one preferred embodiment, the copper electroplating composition of the present invention comprises: A) about 40 to about 60 g / L of copper ions, B) about 80 to about 140 g / L of sulfuric acid; C) about 30 to about 120 mg / L of chloride ions; D) about 300 to about 500 mg / L of linear or branched polyhydroxyl, where the polymer may or may not contain nitrogen-containing species.
[0042] In another preferred embodiment, the invention consists essentially of a copper electroplating composition capable of electrodepositing copper having a high density of nanotwinned copper, the electroplating composition comprising: A) about 40 to about 60 g / L of copper ions, B) about 80 to about 140 g / L of sulfuric acid; C) about 30 to about 120 mg / L of chloride ions; D) about 300 to about 500 mg / L of linear or branched polyhydroxyl, where the polymer consists essentially of linear or branched polyhydroxyl, which may or may not contain nitrogen-containing species.
[0043] By "consisting essentially of" it is meant that the composition does not contain any additives that would have a detrimental effect on the ability of the composition to produce nanotwinned copper deposits.
[0044] The present invention also generally provides a method for electroplating nanotwinned copper on a substrate, comprising the steps of: A) providing a substrate, at least one anode, and a copper plating bath as described above; B) contacting a surface of the substrate and at least one anode with a copper bath, respectively; C) applying a voltage between the surface of the workpiece and at least one anode such that a cathodic polarity is imposed on the substrate relative to the at least one anode; The present invention relates to a method, in which a copper structure having a high density of nanotwins is deposited on a substrate.
[0045] In some embodiments, the nanotwinned copper structure has a multiple (111) grain structure. Furthermore, to ensure the success of this method, which requires high temperatures and high pressures, it is generally preferred to produce electroplated copper with (111) orientation and >90% nanotwinned columnar copper (nt-Cu) grains. Without being bound to any particular theory, it is hypothesized that when two nanotwinned copper substrates are brought into contact and subjected to the required temperature and pressure, the growth of nanotwinned copper spreads between the boundaries of the copper substrates, forming a Cu-Cu bond across the entire interface.
[0046] The current density is generally in the range of about 0.01 to about 50 ASD, more preferably about 0.5 to about 20 ASD, and most preferably about 1 to about 10 ASD. In addition, the electroplating solution is preferably stirred, and the electroplating solution is generally mixed at about 1 to about 2,500 rpm, more preferably about 10 to about 1,200 rpm, and most preferably about 50 to about 400 rpm.
[0047] The anode is preferably an insoluble anode.
[0048] Copper is electrodeposited for a period of time to plate copper to a thickness of about 0.1 to about 1,000 pm, more preferably about 0.3 to about 200 pm, and most preferably about 1 to about 100 pm.
[0049] Substrates that can be plated with copper electroplating solutions include, for example, pillars, pads, lines, and vias.
[0050] The presence of nanotwinned grain structure can be observed using any suitable microscopy technique, such as electron microscopy techniques. The amount of nanotwinned grain structure in the copper deposit is preferably greater than about 80%, more preferably greater than about 90% of nanotwinned columnar copper grains, as estimated based on SEM cross sections.
[0051] As described in the Examples below, the nanotwinned copper structure may be characterized by a plurality of (111) oriented copper grains containing a majority of nanotwins. In some implementations, the plurality of (111) oriented copper grains contains a high density of nanotwins. As used herein, a "high density of nanotwins" may refer to a copper structure having more than about 80% nanotwinning, or even more than about 90% nanotwinning, as observed using suitable microscopy techniques.
[0052] The crystal orientation of the copper grains can be characterized using a suitable technique, such as electron backscatter diffraction (EBSD) analysis. In some implementations, the crystal orientation map can be shown in an inverse pole figure (IPF) map. In accordance with the present invention, the nanotwinned copper structure preferably contains predominantly (111) oriented grains.
[0053] Comparative Example 1: A copper electrolytic composition was prepared containing a solution of 50 g / L copper(II) ions, 100 g / L sulfuric acid, 50 mg / L chloride ions, and 400 mg / L polyethylene glycol (PEG) and placed in the plating cell. A blanket PVD copper substrate was submerged in the plating cell at 25° C. Agitation was set at 300 rpm and a current density of 6 ASD was applied for 500 seconds to plate a 10 pm copper film.
[0054] As shown in FIG. 1, the SEM cross section reveals the absence of nanotwinned copper in the plated copper film.
[0055] Example 2: The same bath and substrate were prepared as described in Comparative Example 1, but PEG was replaced with 400 mg / L poly(2,3-epoxy-1-propanol) and electroplated under the same plating conditions. The results showed that the majority was nanotwinned copper.
[0056] As shown in Figure 2, the SEM cross section shows that the plating film is dominated by nanotwinned copper. The grains are highly columnar and have a high density of grown nanotwins.
[0057] Comparative Example 3 The same bath and substrates as described in Example 2 were prepared and electroplated under the same plating conditions, except that 1 mg / L of bis(sodium sulfopropyl) disulfide (SPS) (brightener) was added to the solution. The results, as seen in Figure 3, showed that the addition of a conventional brightener to the composition resulted in a complete loss of nanotwinned copper in the plated film.
[0058] Comparative Example 4 The same bath and substrate were prepared as described in Example 2. However, 5 mg / L of cationic nitrogen leveler was added to the solution and electroplated under the same plating conditions. As can be seen in Figure 4, the addition of the leveler to the plating composition also resulted in a complete loss of the nanotwinned copper.
[0059] Example 5: The same bath as described in Example 2 was prepared and a 70 pm wide substrate was plated with 6ASD to produce 40 pm tall pillars. The results show a high density of nanotwinned copper, as shown in Figure 5.
[0060] Example 6 The same bath as described in Example 5 was prepared and a substrate containing vias was plated. The results, as shown in FIG. 6, show a significant majority of nanotwinned copper.
[0061] Example 7: The additive can be prepared by reacting an amine-based alcohol or ammonium alcohol with 2,3-epoxy-1-propanol. The general reaction procedure is as follows:
[0062] A solution of boron trifluoride etherate (5 mmol) in methanol was added dropwise to a solution of 2,3-epoxy-1-propanol (2 mol) and N-methyldiethanolamine (0.2 mol) in a 1 L round bottom flask equipped with a thermometer, reflux condenser, and magnetic stirrer. The temperature was allowed to rise freely during the exotherm and heated at the maximum temperature for 30 min. The reaction was then cooled to below 100° C. by the addition of water to make a 20% w / w solution, which was continued to stir for 4 h. The solution was then filtered and used as is.
[0063] The bath described in Example 2 was plated using the additive prepared above.
[0064] The results indicate faster nanotwinning initiation from the copper seeds, and denser rows of nanotwin columnar growth are observed, as shown in Figure 7. The grain structure of the copper deposit is shown in Figure 8 as dominated by (111) grain orientation.
[0065] As can be seen from the examples and comparative examples, the copper electroplating compositions of the present invention are capable of depositing plated copper structures that include a high density of nanotwinned columnar copper grains.
[0066] Finally, it should also be understood that the following claims are intended to cover, as language may imply, all of the general and specific features of the invention described herein, and the full description of the scope of the invention.
Claims
1. 1. A copper electroplating solution comprising: a) 40 to 60 g / L of cupric ion; b) 1 to 150 mg / L of chloride ions; c) 10 to 180 g / L of an acid; d) 10-1000 mg / L of linear or branched polyhydroxyl; The linear or branched polyhydroxyl is a polymer obtained by polymerizing 2,3-epoxy-1-propanol with an amine alcohol or ammonium alcohol, The copper electroplating solution is free of accelerators, brighteners, carriers, wetting agents, and leveling agents; 1. A copper electroplating solution, the copper electroplating solution being capable of depositing nanotwinned copper on a substrate.
2. 10. The copper electroplating solution of claim 1, wherein the copper electroplating solution comprises copper sulfate.
3. 10. The copper electroplating solution of claim 1, wherein the acid comprises sulfuric acid or methanesulfonic acid.
4. 10. The copper electroplating solution of claim 1, wherein the linear or branched polyhydroxyl contains at least one nitrogen atom.
5. 2. The copper electroplating solution of claim 1, wherein the amine-based alcohol or the ammonium alcohol is selected from the group consisting of ethanolamine, diethanolamine, triethanolamine, propanolamine, isopropanolamine, diisopropanolamine, triisopropanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N-propyldiethanolamine, methylmonoethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N-propylmonoethanolamine, N-propyldiethanolamine, N-butylethanolamine, N-butyldiethanolamine, N,N-dibutylethanolamine, hydroxyethylmorpholine, 2-piperidinoethanol, diethanolisopropanolamine, N-(2-hydroxyethyl)pyrrolidine, choline chloride, b-methylcholine chloride, bis(2-hydroxyethyl)dimethylammonium chloride, tris(2-hydroxyethyl)methylammonium chloride, carnitine chloride, (2-hydroxyethyl)dimethyl(3-sulfopropyl)ammonium chloride, and combinations thereof.
6. The copper electroplating solution comprises: a. 40-60 g / L of cupric ion; b. 80 to 140 g / L of sulfuric acid; c. 30-120 mg / L chloride ion; d. 300-600 mg / L of linear or branched polyhydroxyl; 2. The copper electroplating solution of claim 1 , comprising:
7. 1. A method for electrodepositing copper on a substrate, the method comprising: a. contacting the surface of the substrate and at least one anode with the copper electroplating solution of claim 1; b. applying a voltage between the surface of the substrate and the at least one anode such that a cathodic polarity is imposed on the substrate with respect to the at least one anode; A copper deposit having nanotwinned columnar copper grains is deposited on the substrate.
8. 8. The method of claim 7, wherein the copper deposit having nanotwinned columnar copper grains is in a (111) orientation.
9. The method of claim 7, wherein the substrate comprises one or more structures selected from the group consisting of pillars, pads, lines, vias, and one or more combinations thereof.
Citation Information
Patent Citations
Copper bath and method for electrodeposition of matte copper coating
JP2004511663A
Composition for metal electroplating containing a smoothing agent
JP2012512957A
Copper sulfate plating solution and copper sulfate plating method using same
WO2020044416A1
Electrodeposition of nanotwinned copper structures
WO2020092244A1